Analytical model to predict the fatigue life of damaged RC beam strengthened with GGBS based UHPC. (October 2021) - Ganesh, P.; Ramachandra Murthy, A.
Abstract: In the present study, an analytical model was proposed to predict the fatigue response of damaged beams strengthened with ground granulated blast-furnace slag (GGBS) based ultra-high performance concrete (UHPC) strips. The proposed analytical fatigue prediction model (FPM) incorporated with fatigue properties of constituent materials and cross-sectional stress analysis of composite reinforced concrete (RC) beams subjected to fatigue loading condition. The critical parameter controlling the fatigue behaviour of damaged beams strengthened with UHPC strips were a degree of damage in the reinforcing bars and thickness of GGBS based UHPC strips (5, 10 and 15 mm). The damage incorporated in the FPM was categorised as mild, severe and very severe based on the degree of damage level (0.2, 0.3 and 0.7, respectively). In the FPM, fatigue response of strengthened RC beams was captured at the end of each stage of fatigue cycle and updating the material properties iteratively until the threshold of constituent material was attained. From the FPM results, strengthening with a thin UHPC strip (5 mm) was effectively restored the fatigue performance of RC beams induced with a very severe degree of damage level. The analytical studies carried out in the present study were validated with the author's previous experimental investigation. The maximum deviation in predicted results between the experiments and the FPM was 16, 28 and 12% for mild, severe and very severely damaged beams, respectively.